2016
DOI: 10.1371/journal.pone.0167713
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Regulates Porphyromonas gingivalis-Induced Production of Inflammatory Cytokines

Abstract: Periodontitis is a very common oral inflammatory disease that results in the destruction of supporting connective and osseous tissues of the teeth. Although the exact etiology is still unclear, Gram-negative bacteria, especially Porphyromonas gingivalis in subgingival pockets are thought to be one of the major etiologic agents of periodontitis. Endothelin (ET) is a family of three 21-amino acid peptides, ET-1, -2, and -3, that activate G protein-coupled receptors, ETA and ETB. Endothelin is involved in the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…As an explanation of the results of the present study, it should be highlighted that the dysfunctional damage at the endothelium level found in patients with periodontitis and with CHD can be determined by a specific inflammatory and immune pathway in which ET-1 modulates a response towards pathogenic bacteria of the oral biofilm which are exacerbated during the active phases of periodontal damage. It has also been shown that ET-1, during periodontal disease, mediates the immune response at the endothelial level through specific heat shock proteins which has been shown to be useful for stimulating the production of cross-reactive T cells [45][46][47][48][49][50] . In this regard, this process which sees ET-1 as a key modulator, has also been shown to influence the host defense mechanism that determines a subsequent activation of endothelial cell production which leads to an increased risk of future tissue damage effects due to periodontal pathogens bacteria in several oral diseases 43,[47][48][49][50][51][52][53][54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…As an explanation of the results of the present study, it should be highlighted that the dysfunctional damage at the endothelium level found in patients with periodontitis and with CHD can be determined by a specific inflammatory and immune pathway in which ET-1 modulates a response towards pathogenic bacteria of the oral biofilm which are exacerbated during the active phases of periodontal damage. It has also been shown that ET-1, during periodontal disease, mediates the immune response at the endothelial level through specific heat shock proteins which has been shown to be useful for stimulating the production of cross-reactive T cells [45][46][47][48][49][50] . In this regard, this process which sees ET-1 as a key modulator, has also been shown to influence the host defense mechanism that determines a subsequent activation of endothelial cell production which leads to an increased risk of future tissue damage effects due to periodontal pathogens bacteria in several oral diseases 43,[47][48][49][50][51][52][53][54][55][56] .…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin-1 (ET-1) is a 21–amino acid peptide that is converted from big-endothelin-1 by endothelin converting enzyme (ECE), chymase, and/or neprilysin and primarily originates from vascular endothelial and epithelial cells (Pernet et al 2000; Barton and Yanagisawa 2008; Smith et al 2014; Houde et al 2016). The peptide has been reported to be upregulated in oral ulcers and gingival inflammation via the platelet-activating factor (PAF) receptor activation (Yamamoto et al 2003; Slomiany and Slomiany 2005, 2006; Son et al 2016) and to accelerate prostanoid production (Domae et al 1994; Spinella et al 2004; Lin et al 2013). The 2 ET-1 receptors, ET A and ET B , are expressed not only in epithelial and inflammatory cells (Pernet et al 2000; Juergens et al 2008) but also in peripheral sensory fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies investigating the role of ET-1 in peri-implant diseases hold promise for developing novel treatment approaches for peri-implant diseases. Son et al [ 32 ] demonstrated that an endothelin receptor antagonist, bosentan, partially ameliorates alveolar bone resorption and immune cell infiltration, suggesting a potential new avenue for treating periodontitis. As there are currently no established pharmacological treatments for peri-implant diseases, repurposing bosentan, which has already been approved for the treatment of pulmonary hypertension, may be a promising therapeutic for peri-implantitis by mitigating inflammation.…”
Section: Discussionmentioning
confidence: 99%